Susceptibility to positive versus negative emotional contagion: First evidence on their distinction using a balanced self-report measure - Marx, Anton K.G.; Frenzel, Anne C.; Fiedler, Daniel; Reck, Corinna (PLoS ONE, 2024)
Susceptibility to emotional contagion is defined as the disposition of how susceptible someone is to catch others' emotions and it has long been studied in research on mental health, well-being, and social interaction. Given that existing self-report measures of susceptibility to emotional contagion have focused almost exclusively on negative emotions, we developed a self-report measure to assess the susceptibility to emotional contagion of both positive and negative emotions (2 scales). In two studies, we examined their factor structure, validity, and reliability using exploratory factor analysis (Study 1, N = 257), confirmatory factor analysis (Study 2, N = 247) and correlations. Our results confirmed the two-factor structure and demonstrated good internal consistencies. Regarding external validity, our scales showed diverging correlational patterns: While susceptibility to negative emotional contagion was linked to mental health problems and negative emotions, susceptibility to positive emotional contagion was linked to interpersonal functioning and prosocial tendencies. In conclusion, our scales appear to be internally/externally valid and a promising tool for future research.
CRIS-Team Scopus Importer:2024-05-24